ACT-2 JCOG0911A2 AND ESTABLISHING AN INFRASTRUCTURE FOR RADIOLOGICAL STUDIES FOR JCOG BRAIN TUMOR STUDY GROUP CLINICAL TRIALS. (3rd December 2022) - Kinoshita, Manabu; Sasaki, Keita; Natsume, Atsushi; Wakabayashi, Toshihiko; Arakawa, Yoshiki; Narita, Yoshitaka
Abstract: Background: Radiological information is indispensable to understanding the pathology and correctly assessing the treatment response of malignant brain tumors. Clinical trials conducted outside of Japan have vigorously collected and investigated radiological images of the enrolled patients and published many significant findings, such as the RANO criteria. The authors initiated the JCOG0911A2 study, which is an ancillary analysis of JCOG0911, and established an infrastructure for collecting and analyzing raw radiological images of patients enrolled in clinical trials conducted by the JCOG brain tumor study group. JCOG0911A2 study design and infrastructure for radiological image storage: JCOG0911A2 aims to collect all radiological images related to the JCOG0911 study, conduct radiomics analysis, and complete general radiological research. Among 122 registered patients, 2532 series from 118 cases accounting for 237 GB of data were collected as of June 28, 2022. All collected data were anonymized and stored in Osirix MD with triple data backup. JCOG0911A2's treatment response assessment will be performed according to the RANO criteria. Thus, the authors developed a script in MATLAB that enables semi-automatic treatment response assessment according to the investigators' annotations on Osirix MD. Data Management: The abovementioned "semi-automatic treatment response assessment script" was not necessary until up to a collection of 30 cases. However, manual management became impossible as more case data arrived, and establishing a sophisticated and systematic data management system was inevitable. The data management system developed for JCOG0911A2 is also used with minor modifications for the ongoing JCOG study. Conclusion: JCOG0911A2 study established a reliable infrastructure capable of handling radiological images from patients enrolled in JCOG brain tumor study group clinical trials.